Educational Training on the Basics of Learning and Strategies for Teaching Early Childhood and Elementary School - Yuda Purnama Putra (Politeknik Mardira Indonesia, 2025)
This community service aims to provide training to educators and prospective early childhood educators on the basics of learning and teaching strategies that are effective and in accordance with child development. This activity is motivated by the need to improve the quality of prospective educators of mosque-loving teenagers for the implementation of Ramadan pesantren activities at the age of PAUD and elementary school in understanding the characteristics of early childhood students and appropriate teaching methods. The participants who took part in this training activity were 40 people consisting of 3rd grade junior high school students, high school / MA / vocational students and students. The training is carried out face-to-face and contains theoretical and practical materials. The results showed that this training was able to increase participants' understanding of the principles of early childhood learning as well as their ability to design creative and fun learning strategies. Thus, this training is expected to make a positive contribution to the quality of early childhood education in the target area